2002
DOI: 10.1194/jlr.m200041-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of very long-chain saturated fatty acids with serum albumin

Abstract: The remarkable binding properties of serum albumin have been investigated extensively, but little is known about an important class of fatty acids, the very longchain saturated fatty acids (VLCFA; Ͼ 18 carbons). Although VLCFA are metabolized efficiently in normal individuals, they are markers for and possibly causative agents of several peroxisomal disorders. We studied the binding of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 34 publications
5
62
0
Order By: Relevance
“…Serum albumin has six high affinity and numerous low affinity binding sites for this group of ligands (58,59), and although under physiological conditions each serum albumin molecule has only approximately one FFA bound to it, this may rise to four following exercise or to as many as six during heparin treatment (60). Here it is reported that FFAs significantly alter the chaperone-like activity of serum albumin toward both client proteins (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Serum albumin has six high affinity and numerous low affinity binding sites for this group of ligands (58,59), and although under physiological conditions each serum albumin molecule has only approximately one FFA bound to it, this may rise to four following exercise or to as many as six during heparin treatment (60). Here it is reported that FFAs significantly alter the chaperone-like activity of serum albumin toward both client proteins (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…However, we cannot rule out the possibility that CD36 directly binds long versus very long chain FAs via distinct binding sites or mechanisms and promotes their transfer to the membrane as has been previously suggested (1). Like albumin, CD36 may have unique binding sites for FAs of differing chain lengths (26).…”
Section: Discussionmentioning
confidence: 99%
“…VLCFA have very low aqueous solubility, a property that limits its transport between aqueous compartments and is a major impediment to its study even in model membrane systems. VLCFA have been shown to exhibit very slow dissociation rates from both serum albumin and membranes into the surrounding aqueous phase (several orders of magnitude slower than that of typical dietary long-chain FA) (22,23). Additionally, serum albumin has a much lower capacity for VLCFA.…”
mentioning
confidence: 99%